Espera por um milagre: os médicos diante da morte encefálica de pacientes adultos jovens. - Melo Junior, Ivaldo Menezes de (2012)
Communication and health care is a topic that nowadays has been discussed a lot among health professionals, especially when they are asked about the perception of death. Facing the technology development and devaluation of the human being, it s observed a distance among interpersonal relations, making people even more individualists. Facing this, the Intensive Unit Therapy (UTI) has been target of this deshumanization process, due to the many stress factors related to human resources, materials and environmental. Therefore, it is important to identify factors that may contribute in this process, among them stands out the physicians spirituality and religiosity as a central element in the family relationships. Starting on this perception, the present study has as main point to analyze the presence of religiosity and spirituality in physicians communication to the family facing the imminent death of a young adult patient. The methodology had a qualitative approach using the oral history theme. The empirical material was produced by recording ten intensive care physicians of Emergency and Trauma Senador Humberto Lucena Hospital at the city of João Pessoa. This material was analyzed and interpreted based on three axes themes: the physicians perception of the ending of the young patients life, when five of them related to deal with the death naturally for being part of the natural process of life, independent of age. Although the other five related not being prepared to deal with this process, however, traits of alterity were presented, wich shows the humanized care of those professionals; as for the communication and the physician care face to the family, were presented important actions that can improve this process as: let the family members always informed, enable the health professionals and the included the spirituality and religiosity dimension in this relation; those were emphasized in the third axe because they directly influenced in the information conduction about the imminent death of a beloved family member. Thus, no matter wich religion is, it brings subsidy to enable communication of this subject. Therefore, it is believed that humanization rescue at UTI environment by the health professionals spirituality and religiosity, could be very nice to improve the life quality of the patient, family and staff, besides cross of the myth of the unit as being the death place and not the hope of life.